Acquisition of the Inflectional Morphemes by Nigeria Learners of English Language (Nordic Journal of African Studies, 2003)
The aim of this study was to investigate the acquisition of inflectional morphemes with a view to examining the occurrences as well as the misuse of these morphemes in the English essays of some Yoruba learners of English. The informants who participated in the study were sixty senior secondary school one (SSS1) pupils in Oke-Igbo township. The data used for the study were written English compositions and a grammar exercise. The written tasks of the subjects were analysed for various occurrences and misuse of inflectional morphemes. The study found out that there was a wide gap in the mastery of the inflectional morphemes by the subjects. On the basis of this finding, certain recommendations were made.